2000
DOI: 10.1007/s003390051053
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopy and near-edge X-ray-absorption fine structure of C 60 polymer films

Abstract: We report core-level and valence-band X-ray photoelectron spectroscopy (XPS) and carbon K near-edge X-ray-absorption fine structure spectroscopy (NEXAFS) results of plasma-polymerized C 60 . In comparison with evaporated C 60 the C 1s peak is broader and asymmetric for the C 60 polymer and its shake-up satellites diminished. Furthermore, the features of the valence-band as well as the features of the π * antibonding orbitals of the C 60 polymer are broader and reduced in intensity. Changes in the electronic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 23 publications
(34 reference statements)
1
17
0
Order By: Relevance
“…1d. 46 The results indicate that the hydrogen treatment can effectively reduce the oxides in the composite powders. 29,36,44,45 The prominent D peak is from the structural imperfections created by the attachment of epoxy, hydroxyl and epoxy groups on the carbon basal plane; 38 the G peak is corresponding to the rstorder scattering of the E 2g mode.…”
Section: Resultsmentioning
confidence: 93%
“…1d. 46 The results indicate that the hydrogen treatment can effectively reduce the oxides in the composite powders. 29,36,44,45 The prominent D peak is from the structural imperfections created by the attachment of epoxy, hydroxyl and epoxy groups on the carbon basal plane; 38 the G peak is corresponding to the rstorder scattering of the E 2g mode.…”
Section: Resultsmentioning
confidence: 93%
“…As shown in figure 4(b), the hexatriacontane C 1s lineshape is asymmetric and can be fit with four This gas versus solid approach to study vibrational asymmetry, also followed by Ramm et al with fullerene (C 60 ) [69], brought direct proof that each polymer has its own vibrational behavior upon photoionization, which leads to a different degree of asymmetry and a different number of components with different FWHM values in the corresponding C 1s spectra. It is also strongly suggested that the physical intrinsic aspects of a material, such as degrees of branching, unsaturation, crosslinking, crystallinity, and finally chemical environment may strongly impact the lineshapes and linewidths of the considered components [62].…”
Section: Lineshape Broadening Due To Vibrational Asymmetrymentioning
confidence: 84%
“…Observable effects on the spectra References Vibrational excitation subsequent to core-level electron ejection Asymmetry in core-level lineshape inducing increase in FWHM, particularly marked if symmetric components are used for fitting [65][66][67][68][69] Average chemical bond angle disorder Core-level lineshape broadening, increase in FWHM of the fitting components [70,71] Variation in possible electron delocalization in alternant (sp2-sp3) carbons such as HOPG, subsequent to structural changes Core-level lineshape broadening, increase in FWHM of the fitting components [72] Crystallinity and polymer chain conformation…”
Section: Factors Influencing Xps Datamentioning
confidence: 99%
“…As a result, the changes occurring here may represent photopolymerization. There are several reports of UPS in photopolymerized C 60 [5][6][7]], but the relationship with photopolymerization is unclear, and consistent results have not been obtained. As a result, the author measured UPS after photopolymerization by creating an epitaxial film on a MoS 2 (0001) substrate in an ultrahigh vacuum.…”
Section: Changes Over Time During Ups Measurementmentioning
confidence: 99%